Phytochemical Analysis and Antimicrobial activity of Salix alba against Dental Biofilm forming Bacteria - Fayaz, Mussrat (International Journal of Pharmaceutical & Biological Archive, 2014)
Phytochemical Analysis and Antimicrobial activity of Salix alba against Dental Biofilm forming Bacteria